2015
DOI: 10.1016/s0924-9338(15)31194-9
|View full text |Cite
|
Sign up to set email alerts
|

A Calculated Risk: Systematic Review and Metaanalysis of the Conditional Risk for Posttraumatic Stress Disorder (PTSD) in the Brazilian General Population

Abstract: Introduction: Conditional risk for PTSD is the probability of developing PTSD after exposure to trauma; and is influenced by gender, socioeconomic status and type of trauma. Aims: To summarize data on conditional risk for PTSD in the general population through a systematic review and metaanalysis. Methods: Our search included 4 databases, references from selected articles, cited-reference tools, and contact with 30 researchers. We obtained combined measures of conditional risk secondary to any trauma, death of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This study evaluated the implementation of an artificial neural network algorithm to forecast PTSD using ecological risk factors for PTSD that can be easily collected. The ecological factors have been selected through an exhaustive literature review that identified many ecological factors that researchers (Bentley et al, 2014;Bowen et al, 2017;Gelkopf et al, 2012;Itzhaky et al, 2018;Luz et al, 2015;McKeever & Huff, 2003;Rosenbaum et al, 2015;Stanley et al, 2018;Stein et al, 2013;Vaughn-Coaxum et al, 2015;Xue et al, 2015) found to influence PTSD risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study evaluated the implementation of an artificial neural network algorithm to forecast PTSD using ecological risk factors for PTSD that can be easily collected. The ecological factors have been selected through an exhaustive literature review that identified many ecological factors that researchers (Bentley et al, 2014;Bowen et al, 2017;Gelkopf et al, 2012;Itzhaky et al, 2018;Luz et al, 2015;McKeever & Huff, 2003;Rosenbaum et al, 2015;Stanley et al, 2018;Stein et al, 2013;Vaughn-Coaxum et al, 2015;Xue et al, 2015) found to influence PTSD risk.…”
Section: Discussionmentioning
confidence: 99%
“…An exhaustive literature review was conducted with the aim of identifying ecological risk factors for PTSD. The main categories of ecological risk factors that were identified were socioeconomic status (Luz, Berger, Figueira, Coutinho, & Mendlowicz, 2015), age, education, gender (Xue et al, 2015), religiosity (Bentley, Ahmad, & Thoburn, 2014), social support (Stanley et al, 2018), economic loss following the traumatic event (Gelkopf et al, 2012), physical activity (Rosenbaum et al, 2015), substance abuse (Bowen, De Boer, & Bergman, 2017) ,family stressors (Vaughn-Coaxum, Smith, Iverson, & Vogt, 2015), sense of belonging (Itzhaky, Weiss-Dagan, & Taubman-Ben-Ari, 2018), level of exposure (Xue et al, 2015), intensity of trauma, and history of trauma (McKeever & Huff, 2003;Stein et al, 2013;Xue et al, 2015). A short questionnaire of 37 questions measuring these factors was designed for the purpose of this study.…”
Section: Methodsmentioning
confidence: 99%